Volatile Organic Compounds and Antioxidant, Cytotoxic Activities of Extracts from the Leaves of Grewia bulot - Ty Viet Pham; Duc Viet Ho; Anh Tuan Le; Y Duy Ngo; Nhan Thi Thanh Dang; Thang Quoc Le; Bao Chi Nguyen (Indonesian Journal of Chemistry, 2023)
This research aims to determine the volatile compounds present in Grewia bulot leaf extracts and evaluate their cytotoxic and antioxidant activities. The volatile constituents of the n-hexane and dichloromethane extracts were identified by using gas chromatography–mass spectrometry. The main compounds identified in the former were neophytadiene (18.2%), methyl palmitate (14.4%), methyl linoleate (9.7%), β-sitosterol (4.5%), and methyl stearate (3.4%), while those in the latter were palmitic acid (9.8%), hexadecane (7.4%), octadecane (6.0%), neophytadiene (5.3%), and 2-tert-butoxyethanol (5.3%). The cytotoxicities of the extracts were examined against four human cancer cell lines (SK-LU-1, Hep-G2, MCF-7, and KB), while their antioxidant activities were assessed using the DPPH radical scavenging assay. The n-hexane and dichloromethane extracts displayed weak activity against these cancer cell lines, with IC50 values ranging from 90.60 ± 3.49 to 98.27 ± 2.77 µg/mL. All extracts showed antioxidant activities, and the methanol extract exhibited the strongest at an SC50 value of 9.39 ± 0.90 µg/mL. This is the first report on the volatile constituents and bioactivities of G. bulot leaf extracts, suggesting their potential application as antioxidants.